2004
DOI: 10.1016/j.femsec.2004.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and microbial structures of archaeal/bacterial strings-of-pearls communities and archaeal relatives thriving in cold sulfidic springs

Abstract: Recently, a unique microbial community, growing in a whitish, macroscopically visible strings-of-pearls-like structure was discovered in the cold, sulfidic marsh water of the Sippenauer Moor near Regensburg, Bavaria, Germany. The pearls interior is predominated by microcolonies of the non-methanogenic SM1 euryarchaeon; the outer part of the pearls is mainly composed of Thiothrix. To screen sulfidic ecosystems for the distribution of such unique microbial communities, comparative microbial and geochemical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 25 publications
2
93
0
Order By: Relevance
“…No oxygen could be measured in the subsurface water before mixing with the atmosphere in the streamlet, indicating a complete oxygen-free environment in the subsurface. These on-site measurements are in contrast to previous investigations that reported low amounts of oxygen in the spring water (Rudolph et al, 2004;Henneberger et al, 2006). Dominance of the SM1 Euryarchaeon in the subsurface biofilm FISH with Archaea-directed and SM1 Euryarchaeonspecific probes confirmed previous results showing the archaeal dominance within the biofilm.…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…No oxygen could be measured in the subsurface water before mixing with the atmosphere in the streamlet, indicating a complete oxygen-free environment in the subsurface. These on-site measurements are in contrast to previous investigations that reported low amounts of oxygen in the spring water (Rudolph et al, 2004;Henneberger et al, 2006). Dominance of the SM1 Euryarchaeon in the subsurface biofilm FISH with Archaea-directed and SM1 Euryarchaeonspecific probes confirmed previous results showing the archaeal dominance within the biofilm.…”
Section: Resultssupporting
confidence: 68%
“…Its physical characteristics (pH and water composition) have already been described previously (Rudolph et al, 2004;Henneberger et al, 2006), and are found to be very constant over several years of measurement (including sulfate 16 mg l À 1 , thiosulfate 14 mg l À 1 , ammonia 0.33 mg l À 1 ). Oxygen concentrations at different locations of the spring and the stream were re-measured using a highly sensitive oxygen dipping probe (PSt6) coupled with temperature measurement (Fibox 3, LCD trace; PreSens, Regensburg, Germany).…”
Section: Methodsmentioning
confidence: 59%
See 3 more Smart Citations